Pengembangan Produk Funding KSPPS BMT Amanah Ummah Jawa Timur - Indi Masita Lisdawami; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
BMT must be able to compete with financial institutions, so that BMT must have an appropriate strategy in its operational, including product development strategy. This research aims to find out how funding product development strategy works on KSPPS BMT Amanah Ummah West Java. This research uses qualitative approach with a case study. And it also uses sharia finance product development strategy that is according to Suwailem.Suwailem has three main strategies, which are Imitation, Mutation, and Satisfaction. The data collection technique uses interview to informants in KSPPS BMT Amanah Ummah.The result shows, KSPPS BMT Amanah Ummah has 11 types of deposit products. The first strategy is Imitation Strategy that has transferred conventional product to sharia product. After that, the products development more use mutation strategy. Mutation strategy is a strategy that develops new product by knowing existing product at sharia financial instituion, then it is modified to social needs.